2017
DOI: 10.1590/s0102-053620170415
|View full text |Cite
|
Sign up to set email alerts
|

Determination of damaged leaf area and physiological responses of melon plants submitted to different infestation levels of Liriomyza sativae

Abstract: The leafminer Liriomyza sativae (Diptera: Agromyzidae) is one of the main pests of melon crop (Cucumis melo) in the Brazilian semiarid. The aims of this study were to determine the damaged leaf area and assess the physiological responses of melon plants submitted to different levels of infestation per larvae of L. sativae. The study was carried out in a greenhouse, using plants of melon of the cultivar Iracema (yellow melon). The design utilized was completely randomized, with five treatments [control (no infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Significant reductions in net assimilation rate, stomatal and sub-stomatal conductance were observed in mined (1–8 months) old leaves compared to non-mined/intact leaves in the present work. Costa et al 16 also reported low photosynthetic activity in leafminer damaged melon plants, which also confirmed low photosynthetic activity in mined leaves as recorded in this study. Dented chloroplasts in mined leaves reduce carbon assimilation 80 and respiration rate 87 due to low carbon accumulation or CO 2 emissions in spongy parenchymal cells 88 which reduce sub-stomatal conductance and ultimately delay the physiological response of damaged leaves 89 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Significant reductions in net assimilation rate, stomatal and sub-stomatal conductance were observed in mined (1–8 months) old leaves compared to non-mined/intact leaves in the present work. Costa et al 16 also reported low photosynthetic activity in leafminer damaged melon plants, which also confirmed low photosynthetic activity in mined leaves as recorded in this study. Dented chloroplasts in mined leaves reduce carbon assimilation 80 and respiration rate 87 due to low carbon accumulation or CO 2 emissions in spongy parenchymal cells 88 which reduce sub-stomatal conductance and ultimately delay the physiological response of damaged leaves 89 .…”
Section: Discussionsupporting
confidence: 91%
“…Leafminer infestation directly reduced yield and caused stunted plant growth and an early drop of infested leaves on all three vegetative flushes 13 . Henceforth, mined leaves have imperfect physiological response 14 with low photosynthetic activity 15 , 16 and also possess less polyphenols and antioxidant activity 17 by directly reducing on-tree age of infested leaf.…”
Section: Introductionmentioning
confidence: 99%
“…The main damage caused by leafminers on melon is from larvae feeding on the leaf mesophyll tissue that create galleries or mines that reduce the photosynthetic area of the plant, causing the reduction of production and fruit quality (ARAUJO et al, 2013;COSTA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The leafminer Liriomyza sativae (Blanchard, 1938) (Diptera: Agromyzidae) is an important pest in the melon crop (Cucumis melo L., 1753 ) in Brazil (Araujo et al, 2013;Ferreira et al, 2017). The larvae of this agromizid consume the leaf mesophyll, causing the reduction of the plant photosynthetic capacity and the total soluble solids content ( o Brix) of the fruit (Araujo et al, 2013;Costa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%